Noninvasive and Invasive Assessments of the Functional Significance of Intermediate Coronary Artery Stenosis: Is This a Matter of Right or Wrong? - Yongzhen, Fan (Pulse (Basel), 2014)
Coronary computed tomographic angiography (cCTA) has emerged in recent years as a noninvasive modality to evaluate coronary artery disease. Many studies have revealed the excellent diagnostic accuracy of cCTA when compared with invasive coronary angiography (ICA) or intravascular ultrasound (IVUS). It is generally accepted that the functional significance of coronary artery stenosis is important to make treatment decisions; however, cCTA, ICA, and IVUS are limited in the ability to determine the physiologic significance of coronary stenosis. The FIGURE-OUT study compared the noninvasive and invasive assessment of the functional significance of intermediate coronary artery stenosis.